ANALISIS KUALITAS FASHION ILLUSTRATION FOR CASUAL MENSWEAR DALAM MATA KULIAH FASHION ILLUSTRATION - Rismayanti Premitasari; Mila Karmila (Fesyen Perspektif, 2015)
Fashion illustration was needed in the presentation of fashion trends not only as aesthetic considerations but also to showcase fashion designs based on the principles of fashion design appropriately. Professional fashion illustrator was introduced to the college to give the students an overview of the roles and competencies required of the demands of the profession in the fashion world. This study discusses the analysis of the quality of Fashion Illustration For Casual Menswear by students of D3 SRD (Art and Design) class of 2010. The methods used are descriptive methods and techniques of data collections, using the documentation tasks of Fashion Illustration For Casual Menswear, with a sample as many as 26 documentations of Fashion Illustration For Casual Menswear by students of D3 SRD (Art and Design) class of 2010. Based on the results of this study concluded that in terms of the quality concept of casual menswear theme, showed that more than half of the respondents can applied a color display in accordance with the casual menswear theme as well. In terms of display quality on fashion moodboard, showed that more than half of the students can displayed inspiration in the form of images of fashion moodboard. In terms of display quality on design elements of casual menswear, showed that a small proportion of students very well in applied the design elements of color selection with masculine male character. In terms of display quality on design principles casual menswear, showed that more than half of the students can applied the principles of fashion design seen from the balance between the center of attention with a design of casual menswear. In terms of drawing quality on designing of casual menswear, showed that a big proportion of students have the capability to display images of fashion parts.